Telejornal dos 500 Anos : frames de protesto e violência. - Moura, Maria Francisca Canovas de (Universidade do Vale do Rio dos Sinos, 2001)
The master’s thesis “Telejornal dos 500 Anos: Frames de Protesto e Violência” (Television News Broadcast of the 500 years of Discovery: frames of protest and violence) consists of an study of frames and instances of protest and violence broadcast on television during the celebration of 500 years of Discovery of Brazil. The initial aim of this study was to work only with the television news broadcast genre, but the television news instances broadcast on April 22 and 26 - the Discovery and the First Mass in Brazil, respectively – were insufficient to understand what happened in those specific events of celebration. Therefore, itwas necessary to also examine the printed media and establish the intertextuality between these two genres. The reading of both the television and the printed media enabled the reconstruction of protest episodes during the celebration events. The television news articles were looked at from the point of view of the script , the editing and voices, the written text and its images with the intent of showing the role the cinematography language plays on the television text. On a second stage, just the most significant images of protest and violence were extracted and an analysis was made by means of the elements from cinematographic language which stood out the most in the narrative structure. The cinematographic language allowed a rather integrative analysis of television information in as much as it helped rescue its meaning as a whole.
Keywords: Mídia; Telejornal; Violência; Protesto; Comemoração 500 anos de história do Brasil; Imprensa; Linguagem cinematográfica; Notícia; Media; 500 years Brazil history; Violence; News; Protest; Cinematographic language; Press; ACCNPQ::Ciências Sociais Aplicadas::Comunicação